2020
DOI: 10.21037/tau-20-970
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of vascular endothelial growth factor C in renal cell carcinoma and its correlation with pathological parameters and prognosis

Abstract: Background: Renal cell carcinoma (RCC) is a common malignant tumor of the urinary system. This study aimed to analyze the expression of vascular endothelial growth factor C (VEGF-C) in RCC and its relationship with pathological parameters and prognosis. Methods:The clinical data of 68 patients who underwent surgical treatment and confirmed to be RCC by pathology from February 2012 to January 2014 were collected. The specimens of carcinoma tissues of the 68 patients were collected, among which 20 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Lymph Node Metastasis Associated Transcript 1 (LNMAT1) promotes lymphatic metastasis and acts as a potential therapeutic target for LN-metastatic bladder cancer therapy [ 26 ]. Vascular endothelial growth factor C (VEGF-C), interleukin-4 (IL-4), colony-stimulating factor 2 (CSF2), prospero homeobox 1 (PROX1), and TEK receptor Tyrosine Kinase (TEK) is significantly associated with lymph node metastasis in renal cell carcinoma (RCC) [ 27 , 28 ]. Collagen and calcium-binding EGF domain-1 (CCBE1) and neuropilin-2 (NRP2) promote lymphangiogenesis and lymphatic metastasis in CRC and can be used as therapeutic targets in CRC [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymph Node Metastasis Associated Transcript 1 (LNMAT1) promotes lymphatic metastasis and acts as a potential therapeutic target for LN-metastatic bladder cancer therapy [ 26 ]. Vascular endothelial growth factor C (VEGF-C), interleukin-4 (IL-4), colony-stimulating factor 2 (CSF2), prospero homeobox 1 (PROX1), and TEK receptor Tyrosine Kinase (TEK) is significantly associated with lymph node metastasis in renal cell carcinoma (RCC) [ 27 , 28 ]. Collagen and calcium-binding EGF domain-1 (CCBE1) and neuropilin-2 (NRP2) promote lymphangiogenesis and lymphatic metastasis in CRC and can be used as therapeutic targets in CRC [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphangiogenic factors (e.g., VEGF-C and VEGF-D) can induce the metastatic spread of tumors in mouse models of cancer [18]. Several studies have suggested that certain LRGs are associated with the development and prognosis of ccRCC, including VEGF-C, vascular endothelial growth factor D (VEGF-D), and lymphatic vessel endothelial hyaluronan receptor 1 (LYVE1) [19][20][21]. However, no studies have investigated whether LRG can predict tumor progression and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…RCC is not sensitive to radio-chemotherapy, and the five-year survival rate is less than 50% in advanced RCC [2]. The main causes of relapse after RCC treatment and the key factors impacting patient prognosis are lymph node metastasis and cancer cell infiltration [2].…”
Section: Introductionmentioning
confidence: 99%
“…RCC is not sensitive to radio-chemotherapy, and the five-year survival rate is less than 50% in advanced RCC [2]. The main causes of relapse after RCC treatment and the key factors impacting patient prognosis are lymph node metastasis and cancer cell infiltration [2]. Historically, due to their typical resistance to conventional chemotherapies, radiotherapies, and hormone treatments, advanced RCC has a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%